2020
DOI: 10.3390/civileng1030011
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Behavior of Concrete Based on Crushed Sand Combined with Alluvial Sand

Abstract: The aim of this work is to reduce the overexploitation of river sand by proposing a combination of crushed sand and river sand to develop an optimal mix design for concrete. The approach used consisted of a physical, chemical, and mineralogical characterization of aggregates from three quarries located in Yaoundé (Cameroon), followed by the formulation of concrete by substituting 100%, 90%, 80%, 70%, 50%, and 0% of the river sand with crushed sand. A physical and mechanical characterization of the concrete was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Te other major elements, namely potassium oxide, phosphorus oxide, and sodium oxide, show low concentrations, sometimes less than 1%. Tese results are similar to those of Elat et al [8] for gneiss and alluvial sands, those of Unčík and Kmecova [32] for basalt, and those of Gupta and Vyas [7] for granite.…”
Section: Results Of Chemical Analysis By X-ray Fluorescencesupporting
confidence: 88%
See 1 more Smart Citation
“…Te other major elements, namely potassium oxide, phosphorus oxide, and sodium oxide, show low concentrations, sometimes less than 1%. Tese results are similar to those of Elat et al [8] for gneiss and alluvial sands, those of Unčík and Kmecova [32] for basalt, and those of Gupta and Vyas [7] for granite.…”
Section: Results Of Chemical Analysis By X-ray Fluorescencesupporting
confidence: 88%
“…Despite numerous research works carried out on mortars [7][8][9][10], questions remain unanswered concerning the interaction between cement and aggregates, especially those concerning the infuence of the nature of the aggregates on the hydration phenomenon. From this point of view, works [11] have shown that the mechanical properties of mortars based on quarry sand were close to each other and that mortars based on alluvial sands presented weaker mechanical properties than the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 presents the different size aggregates used in the concrete formulations and Table 1 illustrates the chemical compositions of the aggregates obtained from previous studies [5][6]. The cement used is Portland CEM II/B-P 42.5R from Dangoté (Cameroon) with a density of 3100 kg/m 3 and a concrete compressive strength of 55 MPa at 28 days.…”
Section: Aggregate and Cementmentioning
confidence: 99%
“…Durability also depends on its physical and mechanical properties, nature of the aggregate, nature of cement, its water content, the heating rate and time of exposure to fire [1][2][3][4][5][6][7]. However, numerous studies have been carried out on the physical and mechanical properties of concrete based on crushed quarry sand (limestone type) and river sand at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation